THE ACTUALIZATION OF LOCAL WISDOM VALUES IN CIVIC EDUCATION TO STRENGTHEN THE NATIONAL CHARACTER OF STUDENTS AT STATE SENIOR HIGH SCHOOL 1 BANGUNTAPAN - Arifin, Imam; Kusdarini, Eny (Ridwan Institute, 2024)
This research aims to determine the role of teachers and schools in actualizing the value of local wisdom into PPKn (Civic Education) learning so that it becomes a strengthening of national character with religious values, independence, nationalism, mutual cooperation, and has integrity values. This study employed a descriptive approach with qualitative case studies conducted at SMA Negeri 1 Banguntapan Bantul. The subjects were selected purposively, and data collection was carried out through interviews, observations, and documentation. The actualization of these values was analyzed as strengthening the national character of students. The research highlights the importance of cultural context in education and its role in fostering a sense of national identity. By identifying the supporting and inhibiting factors in this process, the study provides insights that can inform educators, policymakers, and curriculum developers about effective strategies and potential challenges in promoting local wisdom within civic education. This contribution is crucial for enhancing educational practices that align with Indonesia's cultural heritage while promoting national character development among students.